2020
DOI: 10.1038/s41541-020-0177-6
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy has a minimal impact on the acute transcriptional signature to vaccination

Abstract: Vaccination in pregnancy is an effective tool to protect both the mother and infant; vaccines against influenza, pertussis and tetanus are currently recommended. A number of vaccines with a specific indication for use in pregnancy are in development, with the specific aim of providing passive humoral immunity to the newborn child against pathogens responsible for morbidity and mortality in young infants. However, the current understanding about the immune response to vaccination in pregnancy is incomplete. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 32 publications
(44 reference statements)
0
13
0
Order By: Relevance
“…A recent study carried out by Tregoning et al investigated the effect of pregnancy on the transcriptomic response after vaccination in pregnant and non-pregnant mouse models and from humans. They also found no difference between the pregnant and non-pregnant state at the level of individual genes, and found similar levels of inflammation post vaccination in both mice models and humans [118]. Kay et al, also demonstrated that pregnant women were able to induce a robust plasmablast response following vaccination as these women had an equivalent rate of post vaccination HAI titres and seroprotection when compared to non-pregnant women [119].…”
Section: Influenza Vaccinementioning
confidence: 92%
“…A recent study carried out by Tregoning et al investigated the effect of pregnancy on the transcriptomic response after vaccination in pregnant and non-pregnant mouse models and from humans. They also found no difference between the pregnant and non-pregnant state at the level of individual genes, and found similar levels of inflammation post vaccination in both mice models and humans [118]. Kay et al, also demonstrated that pregnant women were able to induce a robust plasmablast response following vaccination as these women had an equivalent rate of post vaccination HAI titres and seroprotection when compared to non-pregnant women [119].…”
Section: Influenza Vaccinementioning
confidence: 92%
“…Novel approaches include the study of high-dimensional cell-subset immunophenotyping through CyTOF (Porpiglia et al, 2017;Lingblom et al, 2018;Reeves et al, 2018) and vaccine-induced changes at the metabolic (Li et al, 2017) proteomic (Galassie and Link, 2015) genetic and transcriptional (Stubbington et al, 2017) levels. This knowledge is largely being harnessed to establish signatures predictive of vaccine immunogenicity (Pezeshki et al, 2019), although early inflammatory transcriptomic profiling has recently been explored in the context of vaccine safety (Tregoning et al, 2020). Systems serology has also been used to define Fc features associated with antibody transfer and effector function, as discussed previously (Chung and Alter, 2017;Jennewein et al, 2019) including a detailed characterization of adjuvant effects on antibody quality (Francica et al, 2017).…”
Section: Approaches To Close Our Gaps In Knowledge Methodologymentioning
confidence: 99%
“…Conversely, a systems vaccinology approach can help to understand the effect of pregnancy itself on vaccination, including the specific acute inflammatory pathways induced and markers of immunogenicity/safety. Using Boostrix vaccine (combined diphtheria, tetanus, multivalent acellular pertussis), Tregoning et al (2020) demonstrated that pregnancy might have minimal impact on initial vaccine-induced responses; they observed characteristic patterns of gene expression, BOX 2 | Gaps in knowledge and future avenues of research in infants.…”
Section: Approaches To Close Our Gaps In Knowledge Methodologymentioning
confidence: 99%
See 2 more Smart Citations